Down Regulation of the Munc18b-syntaxin-11 Complex and β1-tubulin Impairs Secretion and Spreading in Neonatal Platelets - Caparrós-Pérez, Eva; Teruel-Montoya, Raúl; Palma-Barquero, Verónica; Torregrosa, José M.; Blanco, José E.; Delgado, Juan L.; Lozano, María L.; Vicente, Vicente; Sola-Visner, Martha; Rivera, José; Martínez, Constantino; Ferrer-Marín, Francisca (Thrombosis and Haemostasis, 2017)
Neonatal platelets are hyporeactive and show impaired agonist-induced secretion despite no obvious abnormalities in their granules. Here, we examined, for the first time, the ultrastructure of neonatal and adult platelets following agonist activation. Under resting conditions, neonatal and adult platelets appeared ultrastructurally identical. Following agonist stimulation, however, noticeable degranulation occurred in adult platelets, while granules in neonatal platelets remained clearly visible and apparently unable to centralize or fuse. To investigate the underlying mechanisms, we first examined the expression levels of the main SNARE proteins, which mediate the membrane fusion events required for exocytosis. Neonatal platelets showed significantly reduced levels of syntaxin-11 and its regulator, Munc18b. Since granule centralization depends on contraction of the microtubule ring, we also examined the expression of its main component, β1-tubulin. Noteworthy, we found decreased TUBB1 mRNA and protein levels in neonatal platelets, while TUBB2A and TUBB isoforms were overexpressed, partially compensating for that deficiency. Finally, supporting the functional consequences of defective exocytosis, adhesion kinetic assays, performed in plasma-free medium, demonstrated delayed adhesion and spreading of neonatal platelets. This is the first report showing marked reductions of syntaxin-11–Munc18b complex and β1-tubulin in neonatal platelets, indicating that these proteins, required for platelet degranulation, are developmentally regulated.
Keywords: platelet physiology; secretion/exocytosis; gene regulation; perinatal haemostasis